Modifications in cellular viability, DNA damage and stress responses inflicted in cancer cells by copper-64 ions - Serban, Radu M.; Niculae, Dana; Manda, Gina; Neagoe, Ionela; Dobre, Maria; Niculae, Dragoș A.; Temelie, Mihaela; Mustăciosu, Cosmin; Leonte, Radu A.; Chilug, Livia E.; Cornoiu, Maria R.; Cocioabă, Diana; et al. (Frontiers in Medicine, 2023)
Due to combined therapeutical emissions, a high linear energy transfer Auger-electrons with the longer ranged β− particles, 64Cu-based radiopharmaceuticals raise particular theragnostic interest in cancer, by joined therapeutic and real-time PET imaging properties. The in vitro study aimed to investigate the biological and molecular background of 64CuCl2 therapy by analyzing the damages and stress responses inflicted in various human normal and tumor cell lines. Colon (HT29 and HCT116) and prostate carcinoma (DU145) cell lines, as well as human normal BJ fibroblasts, were treated up to 72 h with 2–40 MBq/mL 64CuCl2. Radioisotope uptake and retention were assessed, and cell viability/death, DNA damage, oxidative stress, and the expression of 84 stress genes were investigated at various time points after [64Cu]CuCl2 addition. All the investigated cells incorporated 64Cu ions similarly, independent of their tumoral or normal status, but their fate after exposure to [64Cu]CuCl2 was cell-dependent. The most striking cytotoxic effects of the radioisotope were registered in colon carcinoma HCT116 cells, for which a substantial decrease in the number of metabolically active cells, and an increased DNA damage and oxidative stress were registered. The stress gene expression study highlighted the activation of both death and repair mechanisms in these cells, related to extrinsic apoptosis, necrosis/necroptosis or autophagy, and cell cycle arrest, nucleotide excision repair, antioxidant, and hypoxic responses, respectively. The in vitro study indicated that 40 MBq/mL [64Cu]CuCl2 delivers a therapeutic effect in human colon carcinoma, but its use is limited by harmful, yet lower effects on normal fibroblasts. The exposure of tumor cells to 20 MBq/mL [64Cu]CuCl2, might be used for a softer approach aiming for a lower radiotoxicity in normal fibroblasts as compared to tumor cells. This radioactive concentration was able to induce a persistent decrease in the number of metabolically active cells, accompanied by DNA damage and oxidative stress, associated with significant changes in stress gene expression in HCT116 colon cancer cells.